Antibacterial effects of some commmercial fixed and essential oils on causal agent of tomato bacterial cancer and wilt disease - Meral YILMAZ; Süleyman KAVAK; Ömür BAYSAL (Derim, 2014)
Tomato (S. Lycopersicum L.) is the most widely cultivated vegetable grown in the World and is economically important in Turkey. Within seed-borne pathogens, bacteria are the most important ones and threating seed industry and its control is difficult.. One of these pathogens Clavibacter michiganensis subsp. michiganensis (Cmm) causing tomato bacterial cancer and wilt causes yield loss upto 100 percent. Particularly it affects the plant in whole growing season from seedling stage to harvest. In this study, inhibitory activity of some commercial essential oils on Cmm has been investigated. Antibacterial effect of essential oils has been determineted using agar well diffusion method considering the inhibition zone as diameter (mm). 18 out of 34 essential oils showed 67 % and higher inhibitory effect on Cmm. None of commercial fixed oils and all of essential oils were showed antibacterial effect. Essential oils (S. officinalis L. and R. officinalis L.), which is provided at different times from the same company were observed different antibacterial effects.Thyme oils of Origanum spp. are the most effective oils within all tested esential oils. Therefore they can be suggested as biopesticides and control of Cmm on seeds.